Formulasi Sediaan Patch Bukal Ekstrak Daun Sirih Hitam (Piper betle L. var Nigra ): Buccal Patch Preparation Formulation of Black Betel Leaf Extract (Piper betle L. var Nigra) - Risma Indah Ardiyana; Novita Eka Kartab Putri; Fajar Prasetya (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Black betel is one of the native plants from Indonesia which has many benefits for treating various diseases, one of which is for oral diseases such as thrush. This study aims to determine the formula of black betel buccal patch (Piper betle L. var Nigra) which is stable and has good patch activity and to know the formula for buccal patch preparation which is effective as a canker sore and fulfills the characteristics of a good pharmaceutical preparation. The black betel leaf extract was made using the maceration method with 70% ethanol as a solvent. Patches were made based on the extract concentration (0.5%, 1%, 2%) using chitosan as the polymer matrix. The results showed that the best buccal patch was owned at concentrations of 0.5% and 1%. The higher the extract content, the higher the weight, thickness, folding endurance, and swelling index.